Multiple Keratoacanthomas after a Recent Tattoo: A Case Report - Mitri, Fouad (Case Rep Dermatol, 2021)
We report on a 39-year-old man who presented with seven skin lesions on the right thigh 3 weeks after receiving a large tattoo which included red and black pigments. Initially, the lesions grew fast, later their growth stabilized. Histopathology showed well-circumscribed symmetric tumors with a central keratin-filled crater along with further trademarks of a keratoacanthoma. The patient had previously had multiple tattoos with no history of similar lesions. PCR analysis of one of the lesions revealed the presence of human papillomavirus 6. All lesions were excised with a safety margin. A 3-month follow-up revealed no further lesions.